Bio-Nanocomposites: Parepartion Technology and Applications (Medico Legal Update, 2021)
In this paper, combinations of a ceramic mixture with a polymer were developed to be used as a substitutefor damaged bones or teeth. Overlays were prepared using the manual mixing method, followed by the useof ultrasound technology to ensure uniform distribution of the powder within the polymer. The polymer(PMMA) is supported with a ceramic powder (HAMgO) prepared using an effective mechanical mixingmethod. Where the percentages were used for consolidation, starting from (1%-4%). The results of the testsshowed mechanical corrosion or the so-called wear and tear of a significant improvement for the reinforcedpolymeric compounds as the corrosion rate decreased to less than half at 4%. Likewise, the results of theparticle hardness examination showed a successive increase in the percentages compared to the polymerbase material. The results of the durability of compressibility and the Yunk coefficient showed a directincrease with the increase in the percentages of the added ceramic powder. The results were interpretedusing the scanning electron microscope and by relying on the density values approved from the results ofthe exercise.